Safely birth and determination of the origin of the child. The perspective of the Roman Catholic Church - Krajczyński, Jan (Prawo Kanoniczne, 2023)
The author of the study takes up the issue of safe birth and determination of the origin of the child in the perspective of legislation and doctrine of the Roman Catholic Church. First of all, it defines the individual rights of the child in the period from conception of birth, guaranteeing safe birth, it further defines the rules of canon law regarding the determination of the origin of offspring, and finally, it presents the relevant de lege ferenda postulates which are aimed at specifying the legal guarantees of a safe start to an independent life outside the mother's organism and the knowledge by the child of true information’s about its own genetic and biological origin.